Buoyant density, growth rate, and the cell cycle in Streptococcus faecium. - Glaser, D (1989)
The buoyant density in rapidly growing Streptococcus faecium 9790 cells varies over the cell cycle, in contrast to the density in Escherichia coli. Buoyant density in S. faecium was measured by using Percoll (Pharmacia Fine Chemicals, Piscataway, N.J.) density gradients. We found that the mean and coefficient of variation of the population density increased with growth rate; and within a population, the mean cell volume, which was measured electronically, increased with density. These results were compared with electron microscopic measurements of the size distributions of cell wall growth sites within each fraction of the density gradient. As the density increased within a population, the frequency of large cells increased and the frequency of newly initiated cell wall growth sites increased. These effects were more marked as the growth rate increased. Next, these data were regrouped by cell size by using the size of the central growth site as an index of cell cycle stage. Each frequency value was weighted by the proportion of the population represented by that density fraction. Then, the average buoyant density was calculated for each value of cell size. In all cell populations, the density decreased and then increased as the central site enlarged. Peripheral growth sites were initiated as density reached a maximum. At faster growth rates, density increased more steeply, and new peripheral growth sites opened up at a higher frequency. We suggest that the rate at which density increases during the cell cycle correlates with the initiation of new cell wall growth sites.